The Toxic Effect of Pb Nanoparticles Prepared by Laser ablation on Some Biochemical Aspects in Rats - alobaidi, Fiham jasim; Thaker, Abid A.; Ramizy, Asmiet (Iraqi Journal of Physics, 2021)
This work aimed to prepare and study the characteristic feature of lead nanoparticles (PbNPS) and follow its effects on some physiological aspects in rats.PbNPS was prepared by laser ablation of pure lead mass with a pulse of 500 and 100 mJ of energy. The results indicated that the wavelength was approximately 196 and the concentration was reported at 53,8967 mg / L. AFM, as the average diameter has been estimated at 69.93 nm. EFSEM shows the spherical shape of the particle.The experimental animals (rats) were divided into two groups, with seven rats for each one. The first group was a control and the second group was injected with 1 milliliter of PbNPS (53.8673 mg/l) per day for 45 days. Bioaccumulated lead ( in liver, spleen kidney and muscles), total serum proteins, albumin, ALT, AST, ALP and antioxidants (GSH, SOD, CAT, and MDA) were estimated.By comparison to the control, PbNPS exposed animals. There were no significant differences in the bioaccumulated lead. In contrast, there was a significant reduction in total serum protein, albumin, GSH, SOD, CAT. Also, there was an increase in serum ALT, AST, ALP and MDA.